2006
DOI: 10.3766/jaaa.17.7.2
|View full text |Cite
|
Sign up to set email alerts
|

Normative Multifrequency Tympanometry in Infants and Toddlers

Abstract: Multifrequency tympanometry data were measured multiple times between the ages of four weeks and two years from 33 infants/toddlers. Tympanograms were also measured from 33 adult participants. Tympanograms recorded with five probe-tone frequencies (226, 400, 630, 800, and 1000 Hz) were classified using the Vanhuyse et al model classification system (Vanhuyse et al, 1975). Admittance at +200 daPa (Y200) and middle ear admittance (Y(ME)) were calculated. The proportion of Vanhuyse et al patterns in infants and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
52
5
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 17 publications
(28 reference statements)
13
52
5
7
Order By: Relevance
“…Silva30 and Callandrucio et al 31 carried out a study with infants using OAEs and the 1,000Hz test tone tympanometry and found good correlations between the tests, and the same was found in this study's sample. Vartiainem32 and Keefe et al 33 mention that the otoacoustic emissions are very sensitive to middle ear alterations, and this is in agreement with the findings of our study.…”
Section: Discussionsupporting
confidence: 82%
“…Silva30 and Callandrucio et al 31 carried out a study with infants using OAEs and the 1,000Hz test tone tympanometry and found good correlations between the tests, and the same was found in this study's sample. Vartiainem32 and Keefe et al 33 mention that the otoacoustic emissions are very sensitive to middle ear alterations, and this is in agreement with the findings of our study.…”
Section: Discussionsupporting
confidence: 82%
“…Tympanometry performed in the clinic is done using a probe frequency of 226 Hz, a frequency that is optimized for adult-sized middle-ear spaces. However, previous work, along with the current study, indicates that 226 Hz is often not sufficiently sensitive enough to rule out the presence of MEE (Orchik et al 1978;Wiederhold et al 1980;Margolis et al 1995;Rogers et al 2010), especially in infants that have smaller middle-ear volumes than adults (Paradise et al 1976;Calandruccio et al 2006). Margolis et al (1995) found that, similar to our current study, a 226-Hz probe frequency is not sensitive enough to detect 0.5 mL of fluid in the middle ear of adult chinchillas.…”
Section: Discussionmentioning
confidence: 55%
“…Multifrequency tympanometry has been shown to provide improved sensitivity to some middle-ear pathologies (Hunter and Margolis, 1992;Li et al, 1999;Margolis et al, 1999). Normative data in comparison to the Vanhuyse et al 1975 model are available for adults and children (e.g., Calandruccio et al, 2006;Hunter and Margolis, 1992;Margolis and Goycoolea, 1993) and for infants and toddlers (e.g., Calandruccio et al, 2006). Although these methods may increase the probability of detecting middle ear dysfunction, they require extra time to either sweep pressure at multiple probe frequencies or sweep probe frequency at multiple fixed pressures.…”
Section: Cmemr Test Construction-a Clinical Middle-ear Muscle Reflex mentioning
confidence: 99%